Effect of Sedation and Exercise on Phenylalanine Pharmacokinetics in Horses. (June 2014) - Naylor, R; Smith, K; Rankin, D; Blake, V; Atherton, P; Piercy, R
Abstract : Introduction: Measurement of incorporation of stable isotope‐containing amino acids into muscle is the gold‐standard technique for measuring muscle protein synthesis (MPS), but its use in assessing MPS in horses has not been evaluated. Determination of MPS requires steady‐state tracer plasma enrichment and serial muscle biopsy. Given that MPS is often assessed in response to exercise and that muscle biopsy in the standing horse typically requires sedation, the influence of exercise and sedation on tracer kinetics was determined. Methods: Three mature Thoroughbred geldings received 0.1 mg/kg D5‐phenylalanine (D5‐Phe) IV and plasma D5‐Phe enrichment was measured over 3 hrs. Pharmacokinetic modeling determined the rate of appearance and phenylalanine pool size, from which a loading dose and infusion rate that would achieve a steady 5–10% enrichment were calculated. Subsequently, steady‐state was confirmed by measuring plasma enrichment during 6 hours of infusion after loading. Horses then received the same dose and completed a 12‐minute exercise test and were sedated with xylazine 0.4 mg/kg IV. Plasma D5‐Phe enrichment was determined every 5–15 minutes for 2 hours after both exercise and sedation. Results: The mean rate of phenylalanine appearance in the horse was 56 umol/kg/hr (SD 24) and mean phenylalanine pool size 41 umol/kg (SD 8.8). A loading dose of 3.3 umol/kg and an infusion rate of 4.5 umol/kg/hr D5‐phenylalanine was calculated and subsequently, confirmed to achieve steady state tracer concentration at 5.6–9.1% APE in sedentary horses. Exercise caused a transitory, and sedation a more prolonged reduction in plasma enrichment (up to 20%). Conclusions: D5‐phenylalanine is a suitable metabolic tracer in the horse as a steady‐state can be achieved, however interventions should be taken into account. Ethical Animal Research: The study was performed in in accordance with the local Ethics Committee approval and Home office project license (PPL 70/7523) under the UK A(SP)A Act 1986.Sources of funding:  Boehringer Ingelheim.Competing interests:  R Naylor is completing a PhD studentship sponsored by Boehringer Ingelheim.